Can atorvastatin calcium cause asymptomatic hypercalcemia? - Suleyman Hilmi Ipekci; Suleyman Baldane; Mehmet Sozen; Levent Kebapcilar (KARE Publishing, 2014)
The use of statins may have unnatural effects. A 54-year-old woman was admitted to the hospital with an incidental finding of hypercalcemia (10.8 mg/dL). There was no disease other than hyperlipidemia, and the patient had been on a course of atorvastatin calcium 10 mg for 1.5 years. A workup investigation to diagnose the cause of hypercalcemia was completed. The investigation did not reveal any pathological diseases that may have caused the hypercalcemia. The hypercalcemia resolved after atorvastatin- calcium was stopped, and the patient developed hypercalcemia shortly after the initiation of the atorvastatin calcium. Here, we report a clinical case of recurrent hypercalcemia possibly induced by atorvastatin calcium administration.